2020
DOI: 10.1002/iid3.297
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of glycoprotein E subunit and live attenuated varicella‐zoster virus vaccines formulated with a single‐strand RNA‐based adjuvant

Abstract: Introduction: Varicella-zoster virus (VZV), a human alphaherpesvirus 3, elicits both chickenpox and shingles and/or postherpetic neuralgia. A live attenuated vaccine (LAV) and glycoprotein E (gE) subunit vaccine were developed to prevent VZV-induced diseases. We recently reported that single-strand RNA (ssRNA) based on the intergenic region of the internal ribosome entry site of cricket paralysis virus (CrPV) is an effective adjuvant for protein-based and virus-like particle-based vaccines. Here, Chinese hamst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…By the second boost in the two-boost experiment, seven of eight mice vaccinated with 8MTT had mounted an IgG response to TT, while four of eight vaccinated with CITT had mounted an immune response to TT. Thus, 8MTT is a potent vaccine against native TT challenge and could serve as a conjugate vaccine platform to enhance the immune response to polysaccharides and other macromolecular molecules ( 37 39 ) in a rapid response to a microbial pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…By the second boost in the two-boost experiment, seven of eight mice vaccinated with 8MTT had mounted an IgG response to TT, while four of eight vaccinated with CITT had mounted an immune response to TT. Thus, 8MTT is a potent vaccine against native TT challenge and could serve as a conjugate vaccine platform to enhance the immune response to polysaccharides and other macromolecular molecules ( 37 39 ) in a rapid response to a microbial pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Shingrix (GSK) is a recombinant subunit vaccine comprising a VZV gE expressed in CHO cells and the liposome-based adjuvant AS01 B . Other work has sought to investigate subunit vaccines against HZ using gE proteins generated from CHO or insect cells formulated with novel adjuvants (Cao et al, 2021;Lee et al, 2020;Luan et al, 2022a, Luan et al, 2022bWang et al, 2021;Wui et al, 2019;Wui et al, 2021). Here, we investigated and showed that the gE protein could be solubly expressed and purified from E. coli, and then formulated as a subunit vaccine candidate with an appropriate adjuvant to elicit not only a robust neutralizing titer but also a strong CMI response.…”
Section: Discussionmentioning
confidence: 99%
“…The genes encoding the truncated gE (1-545 aa) [17,18], full-length IE63, IE63-2A-gE (2A: GSGATNFSLLKQAGDVEENPGP), and IE63-linker-gE (linker: LQGGGSRGGG) were synthesized commercially by GenScript Biotech Corp. (Nanjing, China) and were inserted into the pcDNA3.1(+) vector for the expression of heterologous proteins in mammalian cells.…”
Section: Dna Plasmidsmentioning
confidence: 99%
“…Therefore, VZV gE is the most commonly chosen antigen for HZ vaccines to induce humoral and cellular immune responses. Previous studies showed an enhanced antibody response when mice were immunized with a truncated form of gE [17,18]. Therefore, we chose the extracellular domain of gE as the antigen in this study.…”
Section: Introductionmentioning
confidence: 99%